Extracranial Complications of Traumatic Brain Injury: Pathophysiology—A Review - Gundappa, Parameswara (Journal of Neuroanaesthesiology and Critical Care, 2019)
Moderate to severe traumatic brain injury is often associated with several extracranial organ complications, which increase the morbidity and mortality. Respiratory complications such as acute lung injury, pneumonia, and acute respiratory distress syndrome (ARDS) occur most commonly, but neurogenic pulmonary edema can be life threatening. Cardiovascular complications occur frequently. However, arrhythmia, cardiogenic shock, and neurogenic stunned myocardium, though occur infrequently, can be life threatening. Coagulation abnormalities and sepsis constitute serious complications that may result in multiorgan failure. These constitute independent risk factors for mortality. Endocrine abnormalities, gastrointestinal disruptions, and other complications occur less commonly. These extracranial complications develop as a result of altered neurogenic immune response, both central and peripheral responses. Brain tissue injury releases both proinflammatory mediators taking part in tissue reparative process and anti-inflammatory cytokines that propagate inflammation. In addition, release of massive amount of catecholamines after head injury results in proliferation of myeloid depressor cells in the circulation, release of reactive oxygen species, and release of immature neutrophils into the circulation. These anti-inflammatory mediators by complex mechanisms inhibit and decrease the number of T cells and cause apoptosis. This results in decreased production and release of cytokines and reduced lymphocyte activated killer cell cytotoxicity, resulting in impaired hypersensitivity reaction. Finally, the complex interplay of various factors leads to suppression of peripheral immune response and susceptibility for infection and sepsis, and causes extracranial organ system failure with increased morbidity and mortality.
Keywords: extra cranial complications; traumatic brain injury; neurogenic pulmonary edema; sepsis; coagulation abnormalities; neurogenic immune response; peripheral immune suppression; neurogenic stunned myocardium